A review of improving nitrogen use efficiency and yield of paddy through application of controlled release fertilizer / Mohamad Afiq Yusri Yusof - Yusof, Mohamad Afiq Yusri (Faculty of Plantation and Agrotechnology, 2018)
Malaysia has no comparative advantage over paddy production, although rice is the staple food of its majority citizen. On average, Malaysia need to imports about 28% of the rice from side country between years 1990 until 2009. Paddy needs high efficiency nitrogen fertilizer that can provide good Nitrogen Use Efficiency (NUE) for them to grow, give high number of tillers and high yield to the farmers. Deficiency of nitrogen element cause by soluble fertilizer that loss to the soil systems throughout various pathways such as nitrification, denitrification, mineralization, immobilization, ammonia volatilization, leaching and surface run off in paddy field could leads reduced plant height, less number of tillers, small leaf area index, chlorosis, low crop photosynthetic rate and most important decrease in yield production. The uses of controlled release fertilizers will help to improve crop yield, reduce the cost of labor and manuring process. In addition, control release fertilizers work to control loss of nutrients in the soil by leaching, surface run off and others. This review is discus about the benefit of using controlled release fertilizer in paddy yield cultivation and to review the effect of controlled release fertilizer on paddy growth and yield production.